Lactate–albumin difference in medical and surgical intensive care units [Dahili ve cerrahi yoğun bakim ünitelerinde laktat-albümin farki] - (:unkn) unknown (Nobelmedicus, 2021)
Objective: Sequential Organ Failure Assessment (SOFA) score, lactate, and lactate-albumin difference values obtained at admission to surgical and medical intensive care units are evaluated for cutoff values and predictive significance on mortality. Material and Method: Data between 2001 and 2012 were extracted from MIMIC–III database. Adult patients admitted to the medical and surgical intensive care unit for the first time were evaluated. The significances of the SOFA score, maximum lactate, and lactate-albumin difference values in predicting mortality were analyzed, and cutoff values are determined. Results: Non-survivors had higher lactate, higher lactate-albumin difference, and lower albumin values than survivors (p<0.001, for all). In surgical intensive care units, lactate, lactate-albumin difference, length of hospital and intensive care unit stays were higher, but 30– and 90– day mortalities were lower than medical intensive care units. SOFA scores were similar (p=0.30). The area under the receiver operating characteristic curve (AUC) of SOFA score (AUC = 0.776, 95% CI: 0.735–0.817) and the cutoff value were greater in the surgical intensive care unit than the medical one (AUC=0.762, 95% CI: 0.745– 0.780). The AUC of overall lactate-albumin difference (AUC=0.713, 95% CI: 0.695–0.731) was larger than overall maximum lactate (AUC=0.680, 95% CI: 0.662– 0.699) on the first day. Both the maximum lactate and lactate-albumin difference cutoff values were higher in the surgical intensive care unit. Conclusion: Lactate-albumin difference's predictor value of mortality was superior to initial minimum albumin and maximum lactate values. Different cutoff values of the SOFA score, lactate-albumin difference, and maximum lactate should be used in medical and surgical intensive care units. © 2021, Nobelmedicus. All rights reserved.
Keywords: Albumin; Intensive care unit; Lactate; Lactate-albumin difference